(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
The article presents information security tools to ensure the secure exchange of information in an automated system. A model of information security for an automated information exchange system is proposed. This model will increase the level of information security in electronic document flow in the cross-border space.